Pushed to Africa: emigration and social change in China - Driessen, M (Taylor and Francis (Routledge), 2016)
This essay explores the dynamics of recent labour migration from China to Africa through the prism of migrant narratives. Drawing on field research in Ethiopia and China the author links migrants’ motives for, and experiences of, migration to social transformation in China: most notably a shift away from the flurry of optimism and idealism to a mood of careful conformism fuelled by a prevailing yearning for a sense of security and a fear of ‘missing out’ in a competition for resources. Migrants expressed being ‘pushed’ to Africa. Their attitudes stand in relief to the dreams about ‘making it’ that have propelled many Chinese to the West. By examining how these migrants imagine time and space, displacement and emplacement, the author sheds light on the distinct characteristics of Chinese migration to Africa, as well as on the relationship between emigration and social change.